2015
DOI: 10.3389/fmicb.2015.01164
|View full text |Cite
|
Sign up to set email alerts
|

The cross-talk of HIV-1 Tat and methamphetamine in HIV-associated neurocognitive disorders

Abstract: Antiretroviral therapy has dramatically improved the lives of human immunodeficiency virus 1 (HIV-1) infected individuals. Nonetheless, HIV-associated neurocognitive disorders (HAND), which range from undetectable neurocognitive impairments to severe dementia, still affect approximately 50% of the infected population, hampering their quality of life. The persistence of HAND is promoted by several factors, including longer life expectancies, the residual levels of virus in the central nervous system (CNS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 361 publications
(491 reference statements)
2
31
0
Order By: Relevance
“…Regarding the interactions of Tat and Meth, our findings were surprising. As mentioned, our previous work has shown that these Meth sensitized animals experience an important repression in the dopaminergic system that is further enhanced by Tat [43], resulting in higher locomotor responses to the drug challenge and replicating aspects of the pathology found in HIV-infected humans [43,109,110]. In chronic and binge Meth administration regimens performed in the same mouse model, the induction of Tat expression during the final cycle of Meth exposure did not impact brain reward function during withdrawal.…”
Section: Discussionmentioning
confidence: 73%
“…Regarding the interactions of Tat and Meth, our findings were surprising. As mentioned, our previous work has shown that these Meth sensitized animals experience an important repression in the dopaminergic system that is further enhanced by Tat [43], resulting in higher locomotor responses to the drug challenge and replicating aspects of the pathology found in HIV-infected humans [43,109,110]. In chronic and binge Meth administration regimens performed in the same mouse model, the induction of Tat expression during the final cycle of Meth exposure did not impact brain reward function during withdrawal.…”
Section: Discussionmentioning
confidence: 73%
“…The presence of cerebral microgliosis in association with lifetime Meth dependence in HIV-infected individuals suggests that Meth alone or interactions between Meth and HIV (such as HIV-1 Tat and gp120 proteins) induce long-lasting microglial activation (Kuhn et al 2011; Mediouni et al 2015). It is also possible that microglial activation occurs in response to chronic Meth-induced neuronal injury (Bowyer et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effects of either Meth or Tat or both on the blood-brain barrier, neurons, and glial cells have been investigated extensively in in vitro cell systems (Cisneros and Ghorpade 2012; Borgmann and Ghorpade 2015; Mediouni et al 2015). Both Meth and Tat inhibited astroglial Wnt/β-catenin signaling (Sharma et al 2011; Henderson et al 2012).…”
Section: Neuropathologymentioning
confidence: 99%